ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS RENDAH DI SEKOLAH DASAR - Netta Azzahra Pangesti; Dian Anggraeni; Yohamintin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the mathematical problem-solving abilities of lower-grade elementary school students, specifically in the number material taught inClass III at MI Alhuda Rawasapi. The background of this research is theimportance of problem-solving skills in mathematics education as a foundation forlogical, critical, and systematic thinking that supports the understanding andapplication of concepts in real-life contexts. This study employs a descriptivequalitative approach using a case study method. Data were collected throughobservation, interviews, and documentation. The results show that students’problem-solving abilities remain low, marked by various obstacles in the fourstages of Polya’s problem-solving steps: understanding the problem, devising aplan, carrying out the plan, and reviewing the solution. Furthermore, five types oferrors were identified based on Newman’s error analysis and Rico’s transformationtheory, including errors in reading the problem, understanding the problem,transforming into mathematical form, carrying out the process, and writing the finalanswer. Contributing factors include low mathematical literacy, underdevelopedabstract thinking skills, and a lack of habits in evaluating their own work. Thisstudy recommends the use of contextual learning approaches and the cultivationof reflective thinking habits to enhance students’ mathematical problem-solvingskills.